Developing Leadership Qualities in Practice Teachers - FADEL, Mohamed Rafik (Journal of Human Sciences, 2011)
One of the most important characteristics in being a good teacher is being a good leader. It is said that good leaders are made not born and so should be good teachers; they should be made not born. In the field of teachers’ training in Algeria, practice teachers who supervise student teachers during their practice at schools are generally selected among the most experienced teachers who are also judged to be the most competent. Their role is to provide guidance to the trainees and to take charge of and evaluate them in their teaching practice. However, these practice teachers have never been prepared to take upon themselves the role of guide or leader to other teachers or trainees. Through this article, we want to highlight the characteristics of a good practice teacher and the role of leader he/she must play in order to be an effective element during the training period. Likewise, using Blake and Mouton Managerial Grid, we show what leadership style our practice teachers represent when mentoring student teachers and suggest how these qualities can be brought to the best levels of achievement.